The practical management of refractory schizophrenia – the Maudsley Treatment REview and Assessment Team service approach. (9th September 2014) - Beck, K.; McCutcheon, R.; Bloomfield, M. A. P.; Gaughran, F.; Reis Marques, T.; MacCabe, J.; Selvaraj, S.; Taylor, D.; Howes, O. D.
<x xml:space="preserve">Abstract</x> Objective To describe a practical approach to the community management of treatment‐resistant schizophrenia (TRS). Method A descriptive review of an approach to the assessment and management of patients with TRS, including the community titration of clozapine treatment, and a report of the management recommendations for the first one hundred patients assessed by the Treatment REview and Assessment Team (TREAT). Results The standardized model for the community assessment, management and titration of clozapine is described. To date, 137 patients have been referred to this service and 100 patients (72%) attended for assessment. Of these, 33 have been initiated on clozapine while fifteen have had clozapine recommended but have not wished to undertake clozapine treatment. Other management options recommended have included augmentation strategies and long‐acting injectable antipsychotics. Conclusion The service had increased the number of patients receiving community assessment and initiation of clozapine by five‐fold relative to the rate prior to the establishment of the service. The large number of referrals and high attendance rate indicates that there is clinical demand for the model. Systematic evaluation is required to determine the clinical and cost‐effectiveness of this model and its potential application to other clinical settings.